Robust individuals control chart for shifts in process mean and variance - Ng, Kooi Huat; Midi, Habshah (WSEAS Press, 2010)
Statistical process control (SPC) involves ongoing checks to ensure whether the mean or variance of the process readings has changed. When a change does occur, the control chart should locate it quickly. If the operator can also be supplied information that aids in the search for the special cause, then critical off-line time can be saved. We examine a process-monitoring tool that not only provides speedy detection regardless of the magnitude of the process shift, but also provides useful change point statistics. A Likelihood ratio method is used to develop test statistics for step change shifts. Apart from traditional charts, robust control charts is a better alternative for a process with contaminated data as the effects of the outlying data values are eliminated. In which robustness against assignable causes of variation appears to be important. The proposed methodology is demonstrated with numerical example.